STRUKTUR UKURAN DAN HUBUNGAN PANJANG-BOBOT UDANG DOGOL (Metapenaeus monoceros) YANG DIDARATKAN DI TPI SUNGAI KAKAP, KABUPATEN KUBU RAYA: Size Structure And Length-Weight Relationships of Dogol Shrimp (Metapenaeus Monoceros) Landed At The Sungai Kakap Fishing Port, Kubu Raya Regency - Nimaz Tegar Sukma Tegar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
Dogol shrimp (Metapenaeus monoceros) is a high-value fishery commodity widely caught in the waters of Sungai Kakap, Kubu Raya Regency, West Kalimantan. Growing market demand and increasing fishing pressure are potential threats to the sustainability of dogol shrimp populations in this area. This study aimed to examine the current condition of dogol shrimp resource exploitation and to assess its utilization status based on size structure, length-weight relationship, first capture size (Lc50%), and asymptotic length (L∞). A descriptive method was applied with simple random sampling at the Sungai Kakap Fish Landing Site (TPI). Sampling was conducted four times from September to December 2025. A total of 785 shrimp were measured, consisting of 284 males and 501 females. The results showed that carapace length ranged from 14.36 to 50.52 mm, with the highest frequency in the 25–27 mm range. Both male and female shrimp exhibited negative allometric growth, expressed by the equations W = 0.010064814L^1.877310535 and W = 0.026226481L^1.579042932, with b values of 1.877 and 1.579, respectively. The Lc50% value was 26 mm, while L∞ for males was 38.79 mm and for females was 53.18 mm. Comparison of Lc50% with half the L∞ value indicated that the shrimp caught had approached the appropriate harvest size. Nevertheless, regulation of mesh size remains necessary to ensure the long-term sustainability of dogol shrimp resources in the Sungai Kakap waters.